Urban Malays` User-Behaviour and Perpective on Privacy and Spatial Organization of Housing - Hashim, Ahmad Hariza; Mohamad Ali, Harlina; Abu Samah, Asnarulkhadi (Directory of Open Access Journals, 2009)
The fundamental form of Malay traditional housing is to accommodate their occupant daily needs and also to provide better congruence between human behaviour and culture as compared to the modern housing. Majority of modern housing today are mass-produced and inhabitants have little choice but to adapt and change their lifestyle within the ‘given environment’ regardless of their behavioural needs and cultural background. In traditional Malay houses, the spaces are more flexible especially in the main house (rumah ibu) where most family activities took place. Separation of space in the traditional Malay house is minimal because their concern is more towards communal intimacy, and this was demonstrated in the serambi (verandah) located in front of the house where guests especially the males were entertained during social and religious functions. Using scheduled-structured questions and graphic aid during the in-depth interviews, this research found that due to the influence of modern link house layout, an interesting pattern from the perspective of urban Malays with regards to privacy concept and Malay culture emerged. Most of the respondents agreed with the re-introduction of the serambi concept in modern housing as a transition zone for informal entertaining, and it has the potential to be a social interaction space for the immediate neighbourhood. Based on the comments given six house plans were generated and respondents were asked to identify an ideal plan which they feel can fulfilled their privacy needs.